2019
DOI: 10.1177/1055665619862457
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Psychological Distress in Families Following a Diagnosis of Cleft Lip and/or Palate

Abstract: Objectives: Despite the potential psychological impact of a diagnosis of cleft lip and/or palate (CL/P) on parents, few large-scale studies currently exist. Utilizing data extracted from The Cleft Collective Birth Cohort Study, the current study aimed to examine the psychological impact of the diagnosis on parent and family functioning and to identify risk and/or protective factors contributing to parental adjustment in order to inform future psychological intervention. Methods: Parent-reported questionnaire d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 53 publications
2
44
1
Order By: Relevance
“…This finding is in line with previous CL/P research (Damiano et al, 2006;Nelson & Kirk, 2013;Feragen et al, 2017) and the wider pediatric literature (Cousino & Hazen, 2013), and provides a positive overall view of the health services relevant to CL/P. Health-care satisfaction is a key predictor of overall familial well-being (Stock et al, 2019a), and as such should be systematically monitored and maintained.…”
Section: Overall Satisfaction With Health-caresupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is in line with previous CL/P research (Damiano et al, 2006;Nelson & Kirk, 2013;Feragen et al, 2017) and the wider pediatric literature (Cousino & Hazen, 2013), and provides a positive overall view of the health services relevant to CL/P. Health-care satisfaction is a key predictor of overall familial well-being (Stock et al, 2019a), and as such should be systematically monitored and maintained.…”
Section: Overall Satisfaction With Health-caresupporting
confidence: 87%
“…In a recent UK-wide quantitative study exploring parents’ psychosocial adjustment following the birth of a child with CL/P (Stock et al, 2019a), satisfaction with health-care was consistently associated with higher levels of parental psychological well-being. This relationship between health-care satisfaction and parental adjustment reinforces the importance of high quality, coordinated, patient-centered care.…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies in the broader literature have focused on the development of resilience in individuals, recent calls have been made to adopt a systemic approach, in which the resources of the whole family unit are considered (Walsh, 2016). Previous research has demonstrated the importance of the relationship between parents of children with CL/P for family well-being (Zeytinoğlu et al, 2016; Stock et al, 2019), in addition to the positive contribution that wider members of the family, such as grandparents and siblings, can make (Stock et al, 2016; Guest et al, 2019). Further exploration of the factors contributing to family resilience is needed, alongside trials of interventions shown to be effective in the general population that may be applicable in CL/P.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature also shows that having a child with healthcare needs (including CL/P) presents many challenges for parents, which can have a considerable impact on quality of life (Cousino & Hazen, 2013;Nelson et al, 2012;Smith, Cheater, & Bekker, 2015;Stock, Costa, White, & Rumsey, 2019). The cross-sectional nature of the current study resulted in an inability to identify the direction of this association.…”
Section: Mother's Concerns For Their Child's Developmentmentioning
confidence: 85%